#### Answer

$3b-2-2c$

#### Work Step by Step

First, expand the terms:
$b-2(1+c-b)=b-2-2c+2b=3b-2-2c$

Published by
Prentice Hall

ISBN 10:
0133186024

ISBN 13:
978-0-13318-602-4

$3b-2-2c$

First, expand the terms:
$b-2(1+c-b)=b-2-2c+2b=3b-2-2c$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.